Analisis Perencanaan Produksi Mebel Menggunakan Software POM Dengan Metode Linear Programming - Mardiansyah Mardiansyah (LPPM Universitas Bina Sarana Informatika, 2022)
The problem of the production system that is still manual makes Sunny Furniture need to make improvements to minimize the occurrence of data management errors in the production process, one solution that can be applied to the company is to use Production Operation Management (POM) software. The method that can be used to project production capacity is the linear programming method, the linear programming method can be used to provide recommendations for production capacity for the next period using a fuzzy linear programming algorithm approach. Production capacity projections are needed so that companies can solve problems in existing production so far and to optimize production and get increased profits. The result of the projection that has been done using POM software using the linear programming method is the projected net profit that will be obtained in the next period of Rp. 61,800,000, compared to the previous period's net profit of Rp. 49,920,000, then the company is predicted to get an increase in profit of Rp. 11,880,000. Forecasting results have also been tested for accuracy by comparing the projection results with real results that occur and the accuracy results are 86.7%.